2017
DOI: 10.1002/ejoc.201700496
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Synthesis of Naphtho[1′,2′:4,5]imidazo[1,2‐a]pyridin‐5‐yl(aryl)methanones through Sequential Sonogashira Coupling/Alkyne–Carbonyl Metathesis

Abstract: An efficient one‐pot route for the construction of naphtho[1′,2′:4,5]imidazo[1,2‐a]pyridin‐5‐yl(aryl)methanones and 5‐phenylnaphtho[1′,2′:4,5]imidazo[1,2‐a]pyridines by sequential Sonogashira coupling reaction followed by trifluoroacetic acid promoted alkyne‐carbonyl metathesis (ACM) has been developed. 2‐(2‐Bromophenyl)imidazo[1,2‐a]pyridine‐3‐carbaldehyde preferentially underwent ACM with phenyl acetylenes, whereas intramolecular hydroarylation reaction was the common pathway in the absence of a carbonyl moi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…In toluene solutions this process is very efficient and gives the products in up to 92 % yields. The explored reaction adequately complements the previously reported approaches towards fluorescent naphtho[1′,2′:4,5]imidazo[1,2‐ a ]pyridine derivatives based on Rh‐, [32,44–46] Cu‐, [42] Pd‐ [31,33] catalyzed annulations of 2‐phenylimidazo[1,2‐ a ]pyridines.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…In toluene solutions this process is very efficient and gives the products in up to 92 % yields. The explored reaction adequately complements the previously reported approaches towards fluorescent naphtho[1′,2′:4,5]imidazo[1,2‐ a ]pyridine derivatives based on Rh‐, [32,44–46] Cu‐, [42] Pd‐ [31,33] catalyzed annulations of 2‐phenylimidazo[1,2‐ a ]pyridines.…”
Section: Discussionsupporting
confidence: 69%
“…The main indication of this is a downfieldshifted doublet of H-1 at 9.41 ppm proving the formation of a planar naphtho[1',2':4,5]imidazo[1,2-a]pyridine skeleton. [30][31][32] An electronic spectroscopy study also revealed the irreversible phototransformation of 1 a (Figure 2). Initially, the spectrum of 1 a featured the maximum at ca.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…6 Among these, a few examples of direct sp 3 C–H functionalization with nucleophiles, like haloalkanes and hydrogen-evolution cross-couplings, including alkoxylation, have been realized by the regioselective C3 C–H activation of imidazo[1,2- a ]pyridines. 7…”
Section: Introductionmentioning
confidence: 99%